Hosting overnight guests: Gendered unpaid work as a solidarity mechanism of migrants in the process of urbanization in Turkey - Uyar Mura, Elif S. (Social Politics, 2022)
This article addresses overnight guest hosting, which is a widespread solidarity practice among rural-to-urban migrants in Turkey. The fieldwork, based on in-depth interviews with 28 first-generation migrant women, reveals that it was mostly the young migrant women who shouldered hosting tasks as gendered unpaid work, which deepen their time poverty and reinforce their dependence on family. The analysis highlights the links between intersectional disadvantages of young migrant women and poverty, the failure of the welfare state to provide social assistance for migrants, and the familialist character of social policy during the peak years of migration. © 2022 The Author(s). Published by Oxford University Press.
Keywords: approches et analyses; asie; classisme; discipline; europe; femmes migrantes*; histoire et politique; intersectionnalité; pauvreté; projet charge mentale; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; travail; travail invisible; turquie

Aspiration, reunification and gender transformation in Jat Sikh marriages from India to Canada - MOONEY, NICOLA (Global Networks, 2006)
In this article I explore marriage as a strategy of family migration among a transnational community of middle-class Jat Sikhs. Family reunification and status aspirations are examined as central concerns of the transnational movement of Jat Sikhs from India to Canada. It is argued that Jat Sikh transnationalism and gender are mutually-constitutive: migration strategies can construct women, as well as men, as agents of marital citizenship, and in facilitating migration, transnational marriage may transform practices and notions of gender and status. The article is based on preliminary ethnographic research among Jat Sikh brides in Toronto and Vancouver, and forms part of a larger study of gender, modernity and identity in Indo-Canadian Jat Sikh marriages.
Keywords: amériques; anthropologie; approches et analyses; asie; canada; colombie-britannique; cours; discipline; famille; histoire et politique; inde; intersectionnalité; justice sociale; mariage; mariages transnationaux; migration; ontario; premier cycle; ressource en ligne; régions géographiques; sciences humaines; sex2283; thématiques; toronto; vancouver

Re-orienting western feminisms: Women's diversity in a postcolonial world - Bulbeck, Chilla (Cambridge University Press, 1997)
The agenda of contemporary western feminism focuses on equal participation in work and education, reproductive rights, and sexual freedom. But what does feminism mean to the women of rural India who work someone else's fields, young Thai girls in the sex industry in Bangkok, or Filipino maids working for wealthy women in Hong Kong? In this 1998 book, Chilla Bulbeck presents a bold challenge to the hegemony of white, western feminism in this incisive and wide-ranging exploration of the lived experiences of 'women of colour'. She examines debates on human rights, family relationships, sexuality, and notions of the individual and community to show how their meanings and significance in different parts of the world contest the issues which preoccupy contemporary Anglophone feminists. She then turns the focus back on Anglo culture to illustrate how the theories and politics of western feminism are viewed by non-western women.
Keywords: approches et analyses; asie; cours; discipline; fem1000; féminisme postcolonial; inde; intersectionnalité; militance; premier cycle; ressource en ligne; régions géographiques; sciences humaines; sociologie; thématiques